Treatment-related fluctuations in Guillain-Barré syndrome: clinical features and predictors of recurrence - Lucas ALESSANDRO; Juan Ignacio CASTIGLIONE; Patricio BRAND; Veronica BRUNO; Fabio BARROSO (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: A treatment-related fluctuation (TRF) in a patient with Guillain-Barré syndrome (GBS) is defined as clinical deterioration within two months of symptom onset following previous stabilization or improvements with treatment. Objective: To investigate the clinical characteristics and factors that could increase the risk of relapse of GBS in patients with and without TRFs. Methods: Retrospective review of medical records of patients (>18 years) with GBS evaluated between January/2006 and July/2019. Demographic and clinical characteristics, ancillary studies, treatment received, and the clinical course of patients with and without TRFs were analyzed. Results: Overall, 124 cases of GBS were included; seven (5.6%) presented TRFs. GBS-TRF cases were triggered more frequently by infectious mononucleosis (28.57 vs. 8.55%; p=0.01). GBS-TRF were initially treated with plasmapheresis more frequently than those without TRF (14.29 vs. 1.70%; p=0.0349). Combined treatment (71.43 vs. 4.27%; p<0.001) and corticosteroids (42.86 vs. 1.71%; p<0.001) were more commonly used in the GBS-TRF group. GBS-TRF patients presented a higher median initial disability score (4 vs. 2; p=0.01). Conclusions: Patients with GBS triggered by infectious mononucleosis and a high degree of initial disability have higher chances of developing TRFs. Although patients with TRF were treated with plasmapheresis more often, the total number was too low to suggest a link between plasma exchange and TRF.